Audit firms' entry into H-share audit market and mainland audit pricing: Evidence from China - ZHANG, Rui (Institutional Knowledge at Singapore Management University, 2024)
Purpose: This study aims to investigate whether mainland Chinese audit firms’ entry into the H-share market to provide audit services affects their mainland audit pricing. Design/methodology/approach: Using data on A-share listed companies in China from 2008 to 2018, a difference-in-differences model to test the research question is designed. Robustness tests are conducted to rule out alternative explanations and additional tests to shed light on the extent and inner workings of the main effect. Findings: The entry of mainland audit firms into the H-share audit market leads to a significant decrease in mainland audit pricing. Moreover, this main effect is (i) growing with the importance of H-share audit services to mainland auditors, (ii) stronger for mainland auditors with lower industry specialisation and shorter tenures, (iii) partially mediated by audit efficiency and (iv) greater when mainland clients have higher bargaining power. Furthermore, mainland auditors’ entry into the H-share audit market does not result in significant deterioration in their mainland audit quality, and significantly increases their market share in the mainland audit market. Originality/value: This study provides new empirical evidence of the relationship between audit firms’ development strategy for internationalisation and audit pricing, extends the literature on auditing issues in emerging markets and should be of potential interest to regulators and investors.